The Effectiveness of the Direct Method in Enhancing Public Elementary Students’ Speaking Skills - Bejo Sutrisno; Silvia Sanusi; Budi Rachmawati (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2026)
This study examines the effectiveness of the Direct Method in improving elementary students’ English speaking skills and explores students’ responses toward learning English through this approach. The research was conducted at Bu Lani’s Tutor House in Depok and involved 12 first-grade students from public elementary schools. A mixed-methods design was employed, combining a quasi-experimental approach with descriptive qualitative analysis, in which the researcher also acted as the instructor. Data were collected through pre-tests and post-tests, classroom observations, and semi-structured interviews. Students’ speaking skills were assessed using five criteria: vocabulary, pronunciation, grammar, fluency, and consistency. The findings indicate a significant improvement in students’ speaking skills after 22 instructional sessions using the Direct Method. Pre-test results showed very low proficiency, with most students scoring 0 or 1 and a total score of 12. In contrast, post-test results demonstrated a substantial increase, reaching a total score of 140. Improvements were particularly evident in fluency, vocabulary, pronunciation, and consistency, although grammatical accuracy remained relatively challenging. Classroom observations confirmed steady progress throughout the learning process, as several students who initially struggled became able to initiate simple conversations using limited vocabulary. Interview results further revealed a positive change in students’ perceptions of English learning; initially viewed as confusing, English lessons became enjoyable through the use of games, songs, and realia. In conclusion, the Direct Method is effective in enhancing young learners’ English speaking skills and promoting positive attitudes toward English learning, even in non-bilingual educational settings.